Implementation of Management Process To Achieve Municipal Solid Waste Management (MSWM) Efficiency – A Systematic Literature Review - Rika Putri, Nyimas Septi; Wardhani, Puteri Kusuma; Muda, Khalida; Hirol, Halinawati; Anwar, Khairil (Program Pascasarjana Universitas Sriwijaya, 2025)
Integrated MSWM is still the target in most developing countries. The factors that influence MSWM performance are integrated not only from the preparation of regulations and funding, but also the preparation of the human resources involved. The planning stage of this model is inspired by the interpretation of the management process by Gunawan et al (2021) and is in line with Terry's (1972) theory which categorizes the management process into planning, organizing, implementing and controlling (POAC) functions. This research characterizes and compiles aspects and indicators of MSWM implementation which are critical issues within the framework of management functions. The goal is to make it easier to recognize the most critical aspects of MSWM implementation. The management function framework in implementing MSWM in this research was prepared using the systematic literature review (SLR) method. In developing countries, the application of MSWM still focuses on the collection system aspect which is the actuating function. In this case, an in-depth study of the planning function is needed, namely how policy and financial support influence the development of an effective technical plan for a collection system. The actuating function does not only carry out technical implementation but is also accompanied by firmness in enforcing regulations and sanctions. Regular monitoring and evaluation are needed to control the effectiveness of MSWM. Supervision requires organized human resource strength. The potential for developing an inventory of elements in each dimension is still needed. This may be caused by differences in the characteristics of the study areas.